Common Values and Constitutional Identities: Can Separate Gears Be Synchronised? (Studies of the Central European Professors’ Network, 2023)
The book examines how Central and Eastern European states reconcile national constitutional identity with European integration, providing a comparative, critical insight into how shared European values and national identities coexist – sometimes harmoniously, sometimes in conflict. It focuses on how EU integration interacts with national constitutional identity in Germany, France, Italy, Croatia, Czech Republic, Hungary, Poland, Romania, and the Slovak Republic. It highlights tensions between national sovereignty and the primacy of EU law, as well as whether ultra vires and constitutional review of EU acts create legal pluralism or fragmentation. The core question are: By what constitutional mechanisms are EU legal acts received or incorporated into each national legal order, and at what hierarchical rank? When EU competences expand beyond the accession settlement, must states amend their constitutions, can courts supply authorization, or do “counter-limits” restrain further transfer? How far may national courts act as constitutional “watchdogs” asserting identity-based limits when EU norms press toward deeper integration, and where do friction points arise?